Toy-Based Technologies for Children with Disabilities Simultaneously Supporting Self-Directed Mobility, Participation, and Function: A Tech Report - Logan, Samuel W.; Feldner, Heather Ann; Bogart, Kathleen R.; Goodwin, Brianna; Ross, Samantha M.; Catena, Michele Ann; Whitesell, Austin A.; Sefton, Zachary J.; Smart, William D.; Galloway, James Cole (Frontiers in Robotics and AI, 2017)
Go Baby Go is a community-based outreach, research, and clinical treatment program that works with families, clinicians, service providers and industry to provide pediatric equipment to children with disabilities for movement, mobility and socialization. The purpose of the current technical report is to describe two innovative and novel extensions of the initial modified ride-on car technology that encourages self-directed mobility, participation and function for young children with disabilities. The current report provides a description of the ‘sit-to-stand’ and ‘throw-baby-throw’ ride-on car technologies: (1) Sit-to-stand modified ride-on car technology: Commercially available, battery-operated, ride-on cars are adapted by installing a large, easy-to-press activation switch that is placed on the steering wheel. The switch has a large surface area and turns on at the slightest touch allowing easier activation for children with disabilities. Common materials such as PVC pipe, swimming kickboards and fun noodles, and Velcro are used to build a custom seating system that provides optimum support for each child. There are no commercially available powered wheelchairs for children with disabilities from birth to three years old. An innovative sit-to-stand version of modified ride-on car will be presented and requires a child to stand up in order to activate the switch to encourage the physical skills of pulling from sit-to-stand, weight bearing, and balance; (2) Throw-baby-throw technology: Children with disabilities that experience limited upper-extremity function are not able to throw an object. The throw-baby-throw technology includes modification of a commercially available, toy-based ball pitching’ machine that projects foam balls to. We modified the toy so that it is switch activated and attached to a modified ride-on car. Our modified throwing device allows children with disabilities to engage in the fundamental motor skill of throwing. Both technologies presented in this technical report embrace the holistic view of the International Classification of Functioning, Disability, and Health framework by placing equal emphasis on the body structure and function, activity, and participation domains. Both technologies specifically target the advancement of physical skills while simultaneously providing opportunities to engage in experiences associated with activity and participation.